2022
DOI: 10.1186/s10195-022-00667-2
|View full text |Cite
|
Sign up to set email alerts
|

Functional and radiological outcomes after treatment of congenital pseudarthrosis of the tibia using the Ilizarov technique: a retrospective single-center study

Abstract: Background Congenital pseudarthrosis of the tibia (CPT) is a challenging problem in orthopedic practice, with high rates of non-union, refracture, and residual deformities. After union, long-term follow-up is required to manage late post-union complications. This study aimed to assess the outcomes of the Ilizarov technique in the management of CPT. Materials and methods This retrospective study included patients with CPT treated with the Ilizarov m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…No complications were observed in the index case during our follow-up duration of eight months after the procedure. However, longer-duration follow-ups were done in other studies (up to six years, until skeletal maturity) and reported varied complications and functional outcomes [11,12].…”
Section: Discussionmentioning
confidence: 99%
“…No complications were observed in the index case during our follow-up duration of eight months after the procedure. However, longer-duration follow-ups were done in other studies (up to six years, until skeletal maturity) and reported varied complications and functional outcomes [11,12].…”
Section: Discussionmentioning
confidence: 99%
“…All patients had unilateral limb involvement, café au lait spots, and were from lowincome backgrounds, with varied non-union types observed. Zayda et al [9] retrospectively analyzed sixteen CPT patients treated with segmental resection or the Ilizarov method, noting a mean age of 5.4 ± 2.8 years at the index operation. There was a slight majority of right-leg (56.2%) involvement over the left (43.8%), with patients having a history of 0 to 7 unsuccessful prior surgeries.…”
Section: Discussionmentioning
confidence: 99%
“…All patients were classified as type II Crawford, with 13.33% showing neurofibromatosis and an average leg length discrepancy of 7.4 ± 3.95 cm. Zayda et al [9] reported an average limb shortening of 3.6 ± 1.9 cm, classifying patients according to the El-Rosasy-Paley classification, and noted a high incidence of fibula dysplasia (81.3%). Preoperative gaps at the CPT site averaged 1.3 ± 1.0 cm, expanding to 6.1 ± 1.0 cm post-resection, with preoperative AOFAS scores ranging from 38-65.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various surgical approaches can be used to treat CPT, such as the cross-union approach, intramedullary rods or nails, vascularized fibular grafting, Ilizarov ring fixation, or a combination of two or three treatments. Regardless of the approach selected, surgery involves use of the same biological principles to rectify angular deformity, bone bridging of the defect, and pseudarthrosis excision [ 5 ]. However, residual difficulties are prevalent.…”
Section: Introductionmentioning
confidence: 99%